Environmental assessment of an integrated adaptive system for the improvement of indoor visual comfort of existing buildings. (January 2018) - Michael, A.; Gregoriou, S.; Kalogirou, S.A.
Abstract: This research aims to propose and evaluate an integrated adaptive system consisting of individual movable modules for the improvement of indoor environmental conditions. The system was evaluated by means of a natural lighting analysis simulation using Ecotect v5.2 and Desktop Radiance v1.02. Daylighting performance indicators, i.e. daylight factor (DF) and uniformity daylight factor (UDF), were calculated for various geometrical configurations. The analysis suggests that the integration of the system in appropriate geometrical configurations maintains high percentages of the plan area exceeding 2% DF, while it drastically increases UDF above the threshold of 0.40. Moreover, an in-depth analysis of natural lighting levels was performed for south-facing spaces during different periods of the year and hours of the day. In the majority of the cases under study, the proposed system maintains a high percentage of the plan area with lighting levels above 500 lux, while it significantly decreases the percentage of area exceeding 3000 lux and thus minimizes the possibilities of glare issues. The research study confirms the positive contribution of the proposed system as a natural lighting regulation system, while it establishes the concept of prosthetic renovation as a renewable energy strategy for the improvement of indoor comfort of existing buildings. Highlights: An adaptive system for the improvement of indoor environmental comfort is proposed. The plug-in system is evaluated by means of a natural lighting analysis simulation. The system maintains high natural lighting levels in spaces of all orientations. The system ensures indoor daylight uniformity and thus minimizes glare issues. Appropriate configurations offer optimal lighting solutions in all cases under study.